Handbook of vegetables and vegetable processing - Hui, Y. H. [ (Yiu H.)]; Sinha, Nirmal K. (Blackwell Publication, 2011)
Handbook of Vegetables and Vegetable Processing serves as a reference handbook containing latest developments and advances in this fast growing field. The book can be considered as a companion to Hui's popular Handbook of Fruits and Fruit Processing (2006)